EFEKTIFITAS PENYULUHAN PENCEGAHAN HIV/AIDS PADA REMAJA DI GAMPONG KEUTAPANG SANGGEU KECAMATAN PIDIE - Rahmi, Lisa; Mulidar (Jurnal Kesehatan An-Nuur, 2024)
The productive age group is very vulnerable to contracting HIV-AIDS, because as teenagers they experience high sexual urges and are always looking for information about sex, and the knowledge and information related to reproductive health that they obtain is very lacking. The aim of this research is to find out the effectiveness of counseling about HIV/AIDS prevention among teenagers in Gampong Keutapang Sanggeue, Pidie District in 2024. The population in this study is all teenagers, totaling 15 people. Sampling was carried out using a total sampling technique of 15 people. The results of the research showed that knowledge of HIV/AIDS prevention among teenagers before being given counseling was in the sufficient knowledge category, 11 respondents (73.3%). The majority of teenagers' knowledge of HIV/AIDS prevention after being given counseling was in the good knowledge category with 9 respondents (60.0%). There is an effectiveness of counseling about HIV/AIDS prevention among teenagers in Gampong Keutapang Sanggeue, Pidie District, with a significance value of ρ= 0.000 (ρ<0.05). It is hoped that the results of this research can increase knowledge about the impact, risks of HIV/AIDS transmission, how to prevent HIV/AIDS transmission, free sex and drugs and promiscuity among teenagers.